Esomeprazole inhibits proliferation of scleroderma fibroblasts via cell cycle regulation - Khan, Mohammad A.; Koniyan, Shaheer; Ahir, Manisha; Jegga, Anil G.; Mayes, Maureen D.; Gius, David; Leung, Justin; Bonnen, Mark D.; Montesi, Sydney B.; Ghebre, Yohannes T. (Frontiers in Pharmacology, 2026)
BackgroundScleroderma is a complex autoimmune disease characterized by abnormal fibroblast proliferation and excessive collagen deposits in the skin and internal organs. We previously showed that esomeprazole, an FDA-approved drug for gastric disorders, may prevent dermal fibrosis.MethodsTo test this, we evaluated the antiproliferative effect of esomeprazole and the underlying molecular mechanisms using primary fibroblasts derived from patients with scleroderma. BrdU incorporation, flow cytometry, immunofluorescence, Western blot analysis, RNA sequencing, and functional enrichment analysis were performed.ResultsEsomeprazole inhibited the proliferation of scleroderma fibroblasts in a dose-dependent manner, as measured by BrdU incorporation and Ki-67 marker. Intriguingly, esomeprazole arrested fibroblasts in the G1 phase of the cell cycle, resulting in a reduction of cells in the S phase. Expression of p21, a known inhibitor of cyclin-dependent kinases (CDKs), was elevated, while CDK1 and CDK2 levels were decreased following esomeprazole treatment.DiscussionThese results suggest that esomeprazole induces G1 phase arrest by upregulating p21 and downregulating CDK1 and CDK2, thereby inhibiting fibroblast proliferation. These data provide important insights into how esomeprazole regulates fibroblast proliferation in scleroderma and suggest that it may represent a potential therapeutic intervention.